Biomaterials-Based Modulation of the Immune System. (22nd September 2013) - Gardner, Austin B.; Lee, Simon K. C.; Woods, Elliot C.; Acharya, Abhinav P.
Abstract : The immune system is traditionally considered from the perspective of defending against bacterial or viral infections. However, foreign materials like implants can also illicit immune responses. These immune responses are mediated by a large number of molecular signals, including cytokines, antibodies and reactive radical species, and cell types, including macrophages, neutrophils, natural killer cells, T-cells, B-cells, and dendritic cells. Most often, these molecular signals lead to the generation of fibrous encapsulation of the biomaterials, thereby shielding the body from these biomaterials. In this review we will focus on two different types of biomaterials: those that actively modulate the immune response, as seen in antigen delivery vehicles for vaccines, and those that illicit relatively small immune response, which are important for implantable materials. The first serves to actively influence the immune response by co-opting certain immune pathways, while the second tries to mimic the properties of the host in an attempt to remain undetected by the immune system. As these are two very different end points, each type of biomaterial has been studied and developed separately and in recent years, many advances have been made in each respective area, which will be highlighted in this review.